2010
DOI: 10.1007/s11136-010-9707-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between chronic pain and health-related quality of life in long-term social assistance recipients in Norway

Abstract: PurposeThe purposes of this study were to compare the health-related quality of life (HRQOL) of long-term social assistance recipients (LTRs) with and without chronic pain and determine the effect of select demographic, social, pain, alcohol, and illicit drug use characteristics on the physical and mental components of their HRQOL.MethodsIn this cross-sectional study, which is part of a larger study that evaluated the health and functional abilities of LTRs in Norway, 405 LTRs of which 178 had chronic pain wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 41 publications
(70 reference statements)
0
19
0
1
Order By: Relevance
“…In addition to physical impairment and disability, chronic pain has been associated with increased unemployment and absence from work (Braden, Zhang, Zimmerman, & Sullivan, 2008), social isolation and loneliness (Loyland, Miaskowski, Paul, Dahl, & Rustoen, 2010), and increased rates of psychiatric disorders and suicidality (Ilgen, Zivin, McCammon, & Valenstein, 2008; Von Korff et al, 2005). …”
Section: Overview Of Pain and Alcoholmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to physical impairment and disability, chronic pain has been associated with increased unemployment and absence from work (Braden, Zhang, Zimmerman, & Sullivan, 2008), social isolation and loneliness (Loyland, Miaskowski, Paul, Dahl, & Rustoen, 2010), and increased rates of psychiatric disorders and suicidality (Ilgen, Zivin, McCammon, & Valenstein, 2008; Von Korff et al, 2005). …”
Section: Overview Of Pain and Alcoholmentioning
confidence: 99%
“…Alcohol users report social motives for drinking (Kuntsche, Knibbe, Gmel, & Engels, 2005), moderate alcohol consumption has been associated with social integration and sociability (Peele & Brodsky, 2000), and alcohol use appears to facilitate social bonding (Sayette et al, 2012). Given that chronic pain has been associated with social isolation (Loyland et al, 2010), researchers have hypothesized that persons with chronic pain may drink alcohol to facilitate social interactions (Kim et al, 2013). Additionally, chronic pain can be a salient stressor (Blackburn-Munro & Blackburn-Munro, 2001).…”
Section: Effects Of Alcohol On Painmentioning
confidence: 99%
See 1 more Smart Citation
“…6, 8, 19, 68, 72 While disparities in prescribing opioid analgesics for pain have not been studied in patients with HIV, several studies found that African-American and Hispanic patients were less likely than White Americans to receive opioid analgesics in a variety of healthcare settings and for different types of pain. 10, 13, 47, 48, 70, 71 Despite this trend, only one study was found that evaluated the occurrence and characteristics of pain in an indigent sample of patients 41, 42 and to our knowledge, no studies have focused on indigent populations with HIV disease.…”
Section: Introductionmentioning
confidence: 99%
“…, Loyland et al . ). Help provided in the person's own place, both continuous or for a limited time, seems the best solution as the person is not taken from his/her familiar environment or family and is not forced to adapt to a new, unknown environment.…”
Section: Discussionmentioning
confidence: 97%